The Use of Probiotics in Dentistry.: A Review of Current Evidence - Burzykowska, Klaudia; Kamila Gęborys; Katarzyna Trela; Laura Więcko; Aleksander Tuteja; Liwia Olczyk; Rema Mohaissen; Mikolaj Tyla; Patryk Stabrawa; Konrad Krupa (Quality in Sport, 2026)
Probiotics, mostly known for their positive effects on gut health, are also increasingly showing beneficial effects in the context of oral health. This review paper discusses the role of probiotics in the prevention and treatment of oral diseases such as dental caries, periodontal disease and halitosis. It emphasizes that the microbial balance in the oral cavity – know as eubiosis – is crucial for the health of teeth and gums. Dysbiosis, the disruption of this balance, promotes the growth of pathogenic bacteria leading to disease. Probiotics work by directly competing with carious bacteria, producing antimicrobial substances and influencing the immune system. Studies have been presented showing the effectiveness of strains such as Lactobacillus rhamnosus, L. reuteri, Weissella cibaria and Streptococcus salivarius in reducing pathogenic bacteria and oral disease symptoms. Regular consumption of fermented diary products can help maintain a healthy oral microbiota. In conclusion, probiotics can provide important support in prevention and treatment of oral diseases, but their effectiveness depends on the type of strain, form of administration and regularity of use.